Insulation composition for battery device, method for preparing the same, sheet formed using the same, and battery module comprising the same
By combining different fiber support composite materials and aerogels, the shortcomings of traditional insulating materials in thermal insulation, fire resistance and mechanical properties are solved, and efficient manufacturing and safety improvement of battery insulating materials are achieved.
Patent Information
- Application Number
- JP2024080557
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-05-17
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The prior art is difficult to provide battery insulating materials that have both excellent thermal insulation, fire resistance and mechanical properties, and traditional insulating materials are fragile and difficult to process during use, resulting in manufacturing difficulties.
Using composite materials containing two or more different fiber support materials, combined with aerogel and adhesive, dispersant and solvent, a battery insulating material with excellent thermal insulation and mechanical properties is formed by controlling the aspect ratio (L/D) difference of the fiber support materials.
It achieves the improvement of efficient thermal insulation, fire resistance and mechanical properties of battery insulating materials, while reducing dust generation during the manufacturing process and improving battery safety.
Smart Images

Figure 2025018922000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aerogel composition for a battery insulation sheet, a method for producing the same, a battery insulation sheet formed using the same, and a method for producing the same. [Background technology]
[0002] Secondary batteries are power storage systems that provide excellent energy density by converting electrical energy into chemical energy and storing it. Unlike primary batteries, which cannot be recharged, secondary batteries can be recharged, and are widely used in IT devices such as smartphones, cellular phones, laptops, and tablet PCs. In recent years, interest in electric vehicles has increased to prevent environmental pollution, and high-capacity secondary batteries are being adopted for electric vehicles. Such secondary batteries are required to have characteristics such as high density, high output, and stability.
[0003] On the other hand, when a battery contains a large number of high-capacity cells such as lithium secondary batteries, one cell may overheat for some reason and experience thermal runaway, adversely affecting other adjacent cells, so it is required that adjacent cells are thermally insulated from each other.
[0004] Therefore, conventionally, a plate material or an insulating resin plate is placed between the cells to insulate and heat the adjacent cells.
[0005] The above information disclosed in the Background of the Invention is intended to enhance the understanding of the background of the present invention only, and may therefore include information that does not constitute prior art. Summary of the Invention [Problem to be solved by the invention]
[0006] One embodiment provides an aerogel composition having excellent heat insulation, fire resistance, mechanical properties, and low dust properties, a manufacturing method thereof, a battery insulation sheet formed using the aerogel composition, and a manufacturing method thereof. [Means for solving the problem]
[0007] One embodiment provides an aerogel composition for a battery insulation sheet, comprising a reinforcing material including two or more types of fibrous supports, an aerogel, a functional material including a binder, a dispersant, or a combination thereof, and a solvent, wherein the two or more types of fibrous supports have different aspect ratios (AR) represented by the following formula 1. AR=L / D (Equation 1) (In formula 1, L represents the average length of the fibrous support, and D represents the average diameter of the fibrous support.)
[0008] The aspect ratio difference between the two or more types of fibrous supports may be 1 to 5,000.
[0009] The reinforcing material may include two or more types selected from the group consisting of a first fibrous support, a second fibrous support, and a third fibrous support.
[0010] The first fibrous support may have an aspect ratio of 1 to 500, an average diameter of 8 μm to 12 μm, and an average length of 100 μm to 3,000 μm.
[0011] The second fibrous support may have an aspect ratio of 2.5 to 2,500, an average diameter of 8 μm to 20 μm, and an average length of 50 μm to 20,000 μm.
[0012] The third fibrous support may have an aspect ratio of 300 to 5,000, an average diameter of 8 μm to 12 μm, and an average length of 3,000 μm to 50,000 μm.
[0013] The reinforcing material may contain 10 to 60 parts by weight of the first fibrous support, 30 to 60 parts by weight of the second fibrous support, and 10 to 60 parts by weight of the third fibrous support, relative to 100 parts by weight of the entire reinforcing material.
[0014] The aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 / g.
[0015] The average particle size (D50) of the aerogel may be from 5 μm to 200 μm.
[0016] The ratio of the average particle diameter of the aerogel to the average length of the fibrous support may be 1:1 to 1:10,000.
[0017] The binder includes an aqueous polymer binder, and the aqueous polymer binder may be at least one selected from the group consisting of aqueous polymers, anionic water-soluble polymers, cationic water-soluble polymers, and water-dispersible polymers.
[0018] The binder may be contained in an amount of 0.5% by weight to 20% by weight based on the total solid content of the aerogel composition.
[0019] The dispersant may be one or more selected from the group consisting of surfactants and phosphate salts.
[0020] The dispersant may be included in an amount of 0.1% by weight to 6% by weight based on the total solid content of the aerogel composition.
[0021] The solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.
[0022] The aerogel composition may contain 5% by weight to 70% by weight of the reinforcing material, 10% by weight to 90% by weight of the aerogel, and 0.5% by weight to 20% by weight of the functional material, based on the total solid content of the aerogel composition.
[0023] Another embodiment provides a method for producing an aerogel composition for a battery insulation sheet, the method including the steps of: mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to produce an aerogel mixture; and mixing the aerogel mixture with a reinforcing material to produce an aerogel composition, the reinforcing material including two or more types of fibrous supports, the two or more types of fibrous supports having different aspect ratios (AR) represented by the following Formula 1: AR=L / D (Equation 1) (In formula 1, L represents the average length of the fibrous support, and D represents the average diameter of the fibrous support.)
[0024] Yet another embodiment provides a battery insulation sheet including a first substrate, a second substrate, and an aerogel layer formed between the first substrate and the second substrate, the aerogel layer being formed using the aerogel composition.
[0025] Yet another embodiment provides a method for manufacturing a battery insulation sheet, the method including: applying the aerogel composition onto a first substrate; and laminating a second substrate onto the applied aerogel composition to manufacture a laminate.
[0026] The method may further include pressing and drying the laminate. Effect of the Invention
[0027] The battery insulation sheet manufactured using the aerogel composition according to an embodiment has excellent thermal insulation properties and fire resistance, as well as excellent mechanical properties such as durability and compressive properties, and can be manufactured at low cost. In addition, the generation of aerogel dust during the manufacturing process or in actual use can be prevented. [Brief description of the drawings]
[0028] [Figure 1] 1 is a schematic diagram showing a structure of a battery insulation sheet according to an embodiment; [Diagram 2]FIG. 2 is a schematic diagram showing a battery insulation sheet according to an embodiment formed between a plurality of cells. [Diagram 3] 2 is a SEM image of an aerogel layer of the battery insulation sheet according to Example 1. [Figure 4] 1 is a SEM image of an aerogel layer of a battery insulation sheet according to Comparative Example 1. [Diagram 5] 1 is a SEM image of an aerogel layer of a battery insulation sheet according to Comparative Example 2. [Figure 6] 13 is an SEM image of an aerogel layer of the battery insulation sheet according to Comparative Example 3. [Figure 7] 13 is an SEM image of an aerogel layer of the battery insulation sheet according to Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Although the present invention will be described in detail below so as to be easily understood by those skilled in the art, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0030] An insulating material is a material that prevents the flow of heat from moving from a high temperature area to a low temperature area, and is used in a variety of industrial fields, including refrigerators, freezer warehouses, and buildings, as well as the aircraft, electronic parts, and automotive industries.
[0031] Such a heat insulating material should have excellent heat insulating performance due to low thermal conductivity, and is also required to have sufficient mechanical strength to maintain such heat insulating performance.
[0032] Meanwhile, aerogel is a transparent or translucent cutting-edge material with a nanoporous structure, and has very low density and low thermal conductivity. As such, it not only has great potential as an insulating material, but is also considered a highly efficient super-insulating material that can be used in a variety of industrial fields.
[0033] Furthermore, the greatest advantage of aerogel is that it exhibits lower thermal conductivity than conventional organic insulation materials such as styrofoam, and that it solves the fatal weaknesses of organic insulation materials, namely, vulnerability to fire and the generation of harmful gases during a fire.
[0034] However, in general, aerogel has a very low strength, i.e., is easily broken even by a small impact due to its high brittleness, and is difficult to process into a very thin thickness and shape. Therefore, despite its excellent insulating properties, it is very difficult to manufacture an insulating material by using aerogel alone.
[0035] An aerogel composition according to one embodiment includes a reinforcing material including two or more types of fibrous supports, an aerogel, a functional material including a binder, a dispersant, or a combination thereof, and a solvent, and the two or more types of fibrous supports may have different aspect ratios (AR) represented by the following formula 1. AR=L / D (Equation 1) (In formula 1, L represents the average length of the fibrous support, and D represents the average diameter of the fibrous support.)
[0036] The battery insulation sheet made of the aerogel composition comprising the above components has excellent insulation properties, fire resistance and mechanical properties, has low manufacturing costs, and can prevent the generation of aerogel dust during the manufacturing process and in actual use, thereby improving the safety of the battery.
[0037] In one embodiment, the reinforcing material includes two or more types of fibrous supports having different aspect ratios, and the mechanical properties of the battery insulation sheet formed using the same can be improved.
[0038] The aspect ratio difference between the two or more types of fibrous supports may be 1 to 5,000, 200 to 4,900, or 200 to 1,000. Here, the aspect ratio difference is applied to each of the two or more types of fibrous supports. For example, when the first fibrous support and the second fibrous support are included, the aspect ratio difference between the first fibrous support and the second fibrous support can mean. In addition, as another example, when the first fibrous support, the second fibrous support, and the third fibrous support are included, the aspect ratio difference between the first fibrous support and the second fibrous support, the aspect ratio difference between the second fibrous support and the third fibrous support, and the aspect ratio difference between the first fibrous support and the third fibrous support can all be meant. By controlling the aspect ratio difference between the two or more types of fibrous supports within the above range, the compression characteristics as well as the heat insulating property and fire resistance of the battery insulation sheet can be improved.
[0039] In one embodiment, the reinforcing material may include two or more types selected from the group consisting of a first fibrous support, a second fibrous support, and a third fibrous support.
[0040] The first fibrous support may have an aspect ratio of 1 to 500, 10 to 500, or 200 to 400. The first fibrous support may have an average diameter of 8 μm to 12 μm. The first fibrous support may have an average length of 100 μm to 3,000 μm.
[0041] The second fibrous support may have an aspect ratio of 2 to 2,500, 50 to 300, or 70 to 150. The second fibrous support may have an average diameter of 8 μm to 20 μm. The second fibrous support may have an average length of 50 μm to 20,000 μm.
[0042] The third fibrous support may have an aspect ratio of 3 to 5,000, 1,000 to 5,000, or 800 to 1,200. The third fibrous support may have an average diameter of 8 μm to 12 μm. The third fibrous support may have an average length of 3,000 μm to 50,000 μm.
[0043] As an example, the reinforcing material may include a first fibrous support and a second fibrous support. In this case, the first fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight, and the second fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight, relative to 100 parts by weight of the entire reinforcing material. In this case, the first fibrous support and the second fibrous support are included in a content ratio within the above range, and the compression characteristics of the battery insulation sheet can be improved.
[0044] As another example, the reinforcing material may include a first fibrous support and a third fibrous support. In this case, the first fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight, and the third fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight, relative to 100 parts by weight of the entire reinforcing material. In this case, the first fibrous support and the third fibrous support are included in a content ratio within the above range, and the compression characteristics of the battery insulation sheet can be improved.
[0045] As yet another example, the reinforcing material may include a second fibrous support and a third fibrous support. In this case, the second fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight, relative to 100 parts by weight of the entire reinforcing material, and the third fibrous support may be included in an amount of 1 to 90 parts by weight, 20 to 80 parts by weight, or 40 to 60 parts by weight. In this case, the second fibrous support and the third fibrous support are included in a content ratio within the above range, and the compression characteristics of the battery insulation sheet can be improved.
[0046] As yet another example, the reinforcing material may include a first fibrous support, a second fibrous support, and a third fibrous support. In this case, the first fibrous support may be included in an amount of 10 parts by weight to 60 parts by weight, or 20 parts by weight to 60 parts by weight, the second fibrous support may be included in an amount of 30 parts by weight to 60 parts by weight, or 40 parts by weight to 60 parts by weight, and the third fibrous support may be included in an amount of 10 parts by weight to 60 parts by weight, 10 parts by weight to 40 parts by weight, or 10 parts by weight to 30 parts by weight, relative to 100 parts by weight of the entire reinforcing material. In this case, the first fibrous support, the second fibrous support, and the third fibrous support are included in a content ratio within the above range, and the compression characteristics of the battery insulation sheet can be further improved.
[0047] Each of the two or more types of fibrous supports may include fibers used as supports for conventional thermal insulation materials.
[0048] The fibrous support may be one or more fibers selected from the group consisting of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
[0049] The natural fibers may be, for example, one or more selected from the group consisting of hemp, jute, flax, coir, hemp, and cellulose.
[0050] The ceramic fibers may be one or more selected from the group consisting of silicon carbide, silicon nitride, boron nitride, and aluminum silicon carbide.
[0051] The mineral fibers may be, for example, mineral fibers comprising one or more selected from the group consisting of basalt, wollastonite, alumina, boron, quartz, silica, slag, and rock.
[0052] The polymer fiber may be, for example, at least one selected from the group consisting of nylon, polyimide, polyamide, polybenzimidazole, polybenzoxazole, polyamideimide, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyethylene (PE), and polypropylene (PP). As a specific example, the polymer fiber may include, but is not limited to, at least one of polyimide, polyamide, and polybenzimidazole.
[0053] The form of the fibrous support may be, for example, one or more selected from the group consisting of powder, wool, chop, felt, batting, and lofty batting, but is not limited thereto.
[0054] The content of the reinforcing material may be 5% by weight to 70% by weight, 25% by weight to 60% by weight, or 30% by weight to 50% by weight based on the total solid content of the aerogel composition. When a battery insulation sheet is produced using an aerogel composition containing a fibrous support within the above range, the mechanical properties of the battery insulation sheet can be improved.
[0055] In one embodiment, the aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 For example, the aerogel may have a BET specific surface area of 500 m 2 / g~950m 2 / g, 550m 2 / g~950m 2 / g, or 600m 2 / g~900m 2By including an aerogel having a BET specific surface area value within the above range, it is possible to provide a heat insulating sheet capable of effectively preventing heat transfer and heat propagation between a plurality of cells.
[0056] The average particle size (D50) of the aerogel may be 5 μm to 200 μm, 10 μm to 100 μm, or 20 μm to 50 μm. By including the aerogel having a particle size within the above range, the heat insulating properties can be improved and the heat transfer between the multiple cells can be delayed.
[0057] The average particle size (D50) can be measured, for example, by a laser diffraction method or a scanning electron microscope (SEM) photograph, and the average particle size (D50) of the particles can be defined as the particle size at 50% of the particle size distribution (the particle size corresponding to 50% of the cumulative volume of the particle size distribution).
[0058] The ratio of the average particle diameter of the aerogel to the average length of the fibrous support may be 1:1 to 1:10,000, 1:70 to 1:10,000, 1:6 to 1:17, or 1:1.5 to 1:2.5. By controlling the ratio of the average particle diameter of the aerogel to the average length of the fibrous support within the above range, it is possible to improve the compression characteristics and low dust characteristics in addition to the heat insulation and heat resistance.
[0059] The content of the aerogel may be 10% by weight to 90% by weight, 30% by weight to 70% by weight, or 40% by weight to 60% by weight based on the total solid content of the aerogel composition. When a battery insulation sheet is produced using an aerogel composition containing aerogel within the above range, the heat insulating property of the battery insulation sheet can be improved.
[0060] In one embodiment, the binder may include a water-based polymer binder. For example, the water-based polymer binder may be at least one selected from the group consisting of a water-based polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and a water-dispersible polymer.
[0061] The water-soluble polymer may be, for example, at least one selected from the group consisting of polyvinyl alcohol, polyethylene oxide, polyacrylamide, and polyvinylpyrrolidone, but is not limited thereto.
[0062] The anionic water-soluble polymer may include at least one selected from the group consisting of polymers having functional groups of carboxylic acid, sulfonic acid, sulfate, phosphate, and salts thereof. For example, the anionic water-soluble polymer may be a polymer having a carboxylic acid group, and a specific example thereof may include, but is not limited to, polymaleic acid.
[0063] The cationic water-soluble polymer may include at least one selected from the group consisting of polymers having functional groups such as amine, ammonium, phosphonium, sulfonium, and salts thereof. For example, the cationic water-soluble polymer may be a polymer having an amine group, and a specific example thereof may be at least one selected from the group consisting of polyethylene amine and polyamine, but is not limited thereto.
[0064] The water-dispersible polymer may be at least one selected from the group consisting of water-dispersible polyurethane and water-dispersible polyester, but is not limited thereto.
[0065] The binder may include a water-based polymer and a water-dispersible polymer, for example, a water-based polymer having binder properties as well as dispersing properties, and a water-dispersible polyurethane having fire-resistant properties, and a specific example thereof may include polyvinyl alcohol and a water-dispersible polyurethane.
[0066] The weight ratio of the aqueous polymer and the water-dispersible polymer may be 1:1 to 1:5, 1:1 to 1:4, or 1:2 to 1:3. By using the aqueous polymer and the water-dispersible polymer in combination within the weight ratio range, the heat insulation property, dust resistance, and compression property of the heat insulating sheet can be further improved as well as fire resistance and mechanical properties.
[0067] The content of the binder may be 0.5 wt% to 20 wt%, 2 wt% to 15 wt%, or 8 wt% to 15 wt% based on the total solid content of the aerogel composition. When the aerogel composition containing the binder within the above range is used to manufacture the battery insulation sheet, the dust characteristics of the battery insulation sheet can be improved.
[0068] In one embodiment, the dispersant may be at least one selected from the group consisting of surfactants and phosphate-based salts. Specific examples of the dispersant include, but are not limited to, at least one of nonionic surfactants, anionic surfactants, amphoteric surfactants, natural surfactants such as lecithin, and phosphates.
[0069] By further including the dispersant, the dispersion of the aerogel in the composition is improved, and the fibrous support and the aerogel can be uniformly dispersed.
[0070] The content of the dispersant may be 0.1% by weight to 6% by weight, 0.1% by weight to 5% by weight, or 0.1% by weight to 3% by weight based on the total solid content of the aerogel composition. When the dispersant is contained within the above range, the aerogel composition can be produced at low cost, and thus a battery insulation sheet having excellent heat insulation properties, fire resistance, mechanical properties, and dust resistance can be produced.
[0071] In one embodiment, the binder and the dispersant may be included in a weight ratio of 1:0.001 to 1:0.67, 1:0.001 to 1:0.5, or 1:0.001 to 1:0.3. When the binder and the dispersant are used in combination in a weight ratio within the above ranges, the aerogel may be more uniformly dispersed in the aerogel layer.
[0072] In one embodiment, the reinforcing material may be contained in an amount of 25% by weight to 60% by weight, the aerogel in an amount of 30% by weight to 70% by weight, and the binder in an amount of 2% by weight to 15% by weight, based on the total solid content of the aerogel composition.
[0073] As a specific example, the aerogel composition may contain 30% to 50% by weight of the reinforcing material, 40% to 60% by weight of the aerogel, and 8% to 15% by weight of the binder, based on the total solid content of the aerogel composition. By forming the aerogel composition within the above ranges, it is possible to realize excellent heat insulation and fire resistance, while improving mechanical properties, and to prevent dust generation by improving the bonding strength between the reinforcing material and the aerogel.
[0074] In one embodiment, the reinforcing material may be contained in an amount of 25% by weight to 60% by weight, the aerogel in an amount of 30% by weight to 70% by weight, the binder in an amount of 2% by weight to 15% by weight, and the dispersant in an amount of 0.1% by weight to 5% by weight, based on the total solid content of the aerogel composition.
[0075] As a specific example, the aerogel composition may contain 30% to 50% by weight of the reinforcing material, 40% to 60% by weight of the aerogel, 5% to 10% by weight of the binder, and 0.1% to 3% by weight of the dispersant, based on the total solid content of the aerogel composition. By forming the aerogel composition within the above ranges, the dispersibility of the aerogel can be improved, excellent thermal insulation and fire resistance can be achieved, and mechanical properties can be further improved, and the cohesive force between the reinforcing material and the aerogel can be improved to prevent dust generation.
[0076] In one embodiment, the solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.
[0077] The polar solvent may include water, an alcohol-based solvent, or a combination thereof.
[0078] The water may include, for example, purified water, ultra-pure water, or a combination thereof.
[0079] The alcohol-based solvent may be, for example, one or more selected from the group consisting of methanol, ethanol, propanol, pentanol, butanol, hexanol, ethylene glycol, propylene glycol, diethylene glycol, and glycerol, but is not limited thereto.
[0080] The non-polar solvent may include a hydrocarbon solvent, for example, one or more selected from the group consisting of hexane, pentane, heptane, toluene, and benzene, and more preferably, an alkane solvent such as hexane, or a mixture containing an alkane solvent, but is not limited thereto.
[0081] The solvent may include water. When water is used as the solvent, raw material costs and post-treatment costs can be effectively reduced. However, when water is used as the solvent, there is a problem that it is difficult to mix with the hydrophobic aerogel. In one embodiment, the aerogel is uniformly dispersed by controlling the mixing step design, mixing conditions, addition and amount of binder and dispersant, etc. When the aerogel is uniformly dispersed in the composition in this way, a battery insulation sheet having excellent insulation properties, fire resistance, mechanical properties, and low dust properties can be formed with a thin thickness without using a large amount of binder.
[0082] The solvent may be contained in such a way that the weight ratio to the total solid content of the aerogel composition is 1:1 to 1:90. For example, the weight ratio of the solvent to the total solid content of the aerogel composition may be 1:50 to 1:70, 1:20 to 1:30, or 1:2 to 1:10. By controlling the weight ratio of the solvent to the total solid content within the above range, the viscosity can be controlled and the aerogel layer can be coated.
[0083] In one embodiment, the aerogel composition may further include a silane-based compound. The silane-based compound may be, for example, one or more selected from the group consisting of 3-(trimethoxysilyl)propylmethacrylate, methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, octadecyltrimethoxysilane, ethyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane. When the silane-based compound is further included, the dispersibility may be further improved.
[0084] In one embodiment, the composition may further optionally include additives such as wetting agents, emulsifiers, compatibilizers, viscosity adjusters, pH adjusters, stabilizers, antioxidants, acidic or basic scavengers, metal deactivators, antifoam agents, antistatic agents, thickeners, adhesion improvers, binders, flame retardants, impact modifiers, pigments, dyes, colorants, deodorizers, and the like.
[0085] According to one embodiment, a method for producing an aerogel composition includes the steps of: mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to produce an aerogel mixture; and mixing the aerogel mixture with a reinforcing material to produce an aerogel composition, the reinforcing material including two or more types of fibrous supports, the two or more types of fibrous supports having different aspect ratios (AR) represented by the above formula 1.
[0086] In the step of preparing the solvent mixture by mixing the functional material with the solvent, the binder may be mixed with the solvent, or the binder and the dispersant may be mixed with the solvent. Here, the specific description of the solvent, binder, and dispersant may be as described above.
[0087] In the step of preparing the aerogel mixture by mixing the solvent mixture and the aerogel, the aerogel may be added in a powder form, and the specific description of the aerogel may be as described above.
[0088] In the step of preparing an aerogel composition by mixing the aerogel mixture with a reinforcing material, the specific description of the reinforcing material may be as described above.
[0089] In each of the steps of preparing a solvent mixture by mixing a functional material including a binder, a dispersant, or a combination thereof with the solvent, preparing an aerogel mixture by mixing the solvent mixture with an aerogel, and preparing an aerogel composition by mixing the aerogel mixture with a reinforcing material, a mixer may be used during mixing. For example, the mixer may include, but is not limited to, a planetary mixer and a thinky mixer.
[0090] As a specific example, a planetary mixer may be used to mix the solvent mixture and the aerogel. When the solvent mixture and the aerogel are mixed using the planetary mixer, the aerogel can be uniformly dispersed in the solvent.
[0091] The planetary mixer may be a device that can be used to mix or stir different materials to produce a homogenous mixture, and may include blades that are capable of planetary motion.
[0092] In one embodiment, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades. As a specific example, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades.
[0093] The planetary blades and high speed dispersion blades rotate continuously about their axes, and the rotational speed may be expressed in units of rotations per minute (rpm).
[0094] In one embodiment, the planetary mixer may include a first blade and a second blade having different rotation axes. For example, the first blade may be a low-speed blade, and the second blade may be a high-speed blade. Here, low speed and high speed refer to the relative rotation speeds of the first blade and the second blade. As a specific example, the first blade may be an open blade, and the second blade may be a Despa blade.
[0095] The rotation speed of the first blade may be, for example, 10 rpm to 100 rpm, 10 rpm to 60, or 30 rpm to 70 rpm. The rotation speed of the second blade may be, for example, 100 rpm to 2000 rpm, 100 rpm to 1000 rpm, 300 rpm to 1700 rpm, or 500 rpm to 1700 rpm.
[0096] When the functional material is added to the solvent and mixed, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 600 rpm to 1000 rpm, or 700 rpm to 800 rpm. By mixing the solvent and the functional material as described above, a solvent mixture in which the binder, dispersant, or a combination thereof is uniformly dispersed is prepared, and aerogel mixing in the subsequent step can be performed more easily.
[0097] When the solvent mixture and the aerogel are mixed, the rotation speed of the first blade of the mixer may be 30 rpm to 70 rpm, 40 rpm to 70 rpm, or 60 rpm to 70 rpm, and the rotation speed of the second blade may be 500 rpm to 1700 rpm, 600 rpm to 1600 rpm, or 800 rpm to 1500 rpm. By adding the aerogel to the solvent mixture and mixing it as described above, it is possible to prevent the aerogel from agglomerating with each other and induce uniform dispersion.
[0098] When the aerogel mixture and the fibrous support are mixed, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 400 rpm to 1500 rpm, or 800 rpm to 1200 rpm. When the aerogel mixture and the fibrous support are mixed in this way, the air bubbles in the composition are removed, the viscosity is adjusted, and the fibrous support is easily dispersed between the uniformly dispersed aerogel, so that the aerogel may be present in the composition in a form in which the periphery of the fibrous support is covered by the aerogel. Here, a binder is present between the aerogel and the fibrous support, which can improve the binding force between the aerogel and the fibrous support.
[0099] In one embodiment, a battery insulation sheet includes a first substrate, a second substrate, and an aerogel layer formed between the first substrate and the second substrate, and the aerogel layer may be formed using the aerogel composition according to the embodiment.
[0100] 1 is a schematic diagram showing the structure of a battery insulation sheet according to one embodiment. Here, a case containing three types of fibrous supports is shown as a representative example, but other cases containing two or four or more types of fibrous supports are not excluded.
[0101] Referring to FIG. 1, in one embodiment, the battery insulation sheet 100 may have a structure including a first substrate 110, an aerogel layer 120 formed on the first substrate 110, and a second substrate 130 formed on the aerogel layer 120. In addition, in the aerogel layer 120, the first fibrous support, the second fibrous support, and the third fibrous support, which have different aspect ratios, are shown as lines with different average lengths and shapes, but they do not necessarily have the structure shown in the figure, and their thicknesses may also be different. In addition, in order to specifically explain the structure in which the first fibrous support, the second fibrous support, and the third fibrous support are dispersed, other components are not shown, but this should not be interpreted as meaning that the aerogel layer does not contain components other than the reinforcing material. In addition, in FIG. 1, the first substrate 110 and the second substrate 130 may be formed of the same or different materials.
[0102] By forming an aerogel layer between the first substrate and the second substrate using the aerogel composition according to an embodiment, the battery insulation sheet has improved mechanical properties in addition to thermal insulation and fire resistance, and can prevent the aerogel from falling off and generating dust when the battery insulation sheet is manufactured or installed inside an apparatus.
[0103] FIG. 2 is a schematic diagram showing a battery insulation sheet according to one embodiment formed between a plurality of cells.
[0104] 2, the battery insulation sheet 100 according to an embodiment may be formed between each of the cells 200 in a battery module including the plurality of cells 200. Here, the upper and lower surfaces of the battery insulation sheet, i.e., the first and second substrates of the battery insulation sheet, may be disposed to face the adjacent cells, respectively. By forming the battery insulation sheet 100 according to an embodiment between each of the plurality of cells 200, it is possible to provide a battery module and a battery pack including the same, which are safer, by blocking a flame in advance inside the cell and minimizing the spread of the flame to other cells.
[0105] In the battery insulation sheet, the specific description of the aerogel composition forming the aerogel layer may be as described above.
[0106] The first and second substrates may be made of various materials such as resin, metal, inorganic material other than metal, or composites thereof, and the type of the materials is not limited. The form of the substrate may be a film, thin film, sheet, or the like, and is not particularly limited.
[0107] The resin may be, for example, one or more selected from the group consisting of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and polyamide.
[0108] The metal may be, for example, one or more selected from the group consisting of copper, nickel, cobalt, iron, chromium, vanadium, palladium, ruthenium, rhodium, molybdenum, tungsten, iridium, silver, gold, and platinum. When using a substrate made of the above metal material, the substrate may be subjected to anti-corrosion treatment, insulation treatment, etc., as necessary.
[0109] The inorganic material may be one or more selected from the group consisting of calcium carbonate (CaCO3), talc, and mica.
[0110] As a specific example, the first substrate and the second substrate may include an inorganic material, and more specifically, may include mica, which can improve the heat insulation property and durability of the heat insulating sheet.
[0111] In one embodiment, each of the two or more fibrous supports in the aerogel layer may have a vertical orientation, a horizontal orientation, or a combination thereof. As a specific example, each of the two or more fibrous supports in the aerogel layer may be uniformly oriented vertically and horizontally. In this case, the compression properties of the aerogel layer are improved, and the pressure on the adjacent cells during the cell deterioration and expansion process can be absorbed, thereby improving the safety of the battery.
[0112] In one embodiment, the aerogel layer may be formed in a single layer structure or a multi-layer structure. When the aerogel layer is formed in a multi-layer structure, the aerogel layer may be formed in 2 to 10 layers, 2 to 7 layers, or 2 to 5 layers.
[0113] A method for manufacturing an embodiment of a battery insulation sheet may include a step of applying an aerogel composition according to an embodiment onto a first substrate, and a step of laminating a second substrate on the applied aerogel composition to manufacture a laminate.
[0114] In the method for producing the battery insulation sheet, the specific description regarding the substrate and the aerogel composition may be as described above.
[0115] The steps of applying the aerogel slurry onto the first substrate and laminating the second substrate onto the applied aerogel slurry may be carried out in a conventional manner.
[0116] The step of applying the aerogel slurry onto the first substrate may be performed once or repeated two or more times.
[0117] In one embodiment, after producing the laminate, the method may further include pressing and drying the laminate.
[0118] The drying step may be performed at a temperature of, for example, 25° C. to 100° C., 45° C. to 90° C., or 60° C. to 85° C. When the drying is performed at the above temperature conditions, a robust aerogel layer is formed on the substrate without a separate adhesive member or bonding agent while preventing detachment between the substrate and the aerogel layer, and a coating layer may be formed in which the aerogel is coated around the two or more dispersed fibrous supports.
[0119] According to an embodiment, a battery insulation sheet can be manufactured by a simple method of applying an aerogel composition onto a first substrate, laminating a second substrate on the aerogel composition to manufacture a laminate, and then pressing and drying the laminate. This method does not require the use of a separate adhesive or the formation of an adhesive layer, and because the aerogel is uniformly dispersed, the battery insulation sheet can have excellent insulation properties, fire resistance, mechanical properties, and low dust properties even at a thin thickness.
[0120] Specific examples of the present invention will be presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereto. Furthermore, since the contents not described here can be sufficiently inferred by a person skilled in the art, the description thereof will be omitted.
[0121] (Battery insulation sheet manufacturing) Example 1 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) was added as a binder to ultrapure water as a solvent, and then mixed under conditions of an open blade of 30 rpm and a despa blade of 700 rpm to produce a solvent mixture. 2 Aerogel having a diameter of 1 / g and an average particle diameter (D50) of 60 μm was added and mixed under the conditions of an open blade of 70 rpm and a Despa blade of 1500 rpm to produce an aerogel mixture. A first fibrous support having an aspect ratio of 1, a second fibrous support having an aspect ratio of 2, and a third fibrous support having an aspect ratio of 3 were added to the aerogel mixture in a weight ratio of 1:3:6 as reinforcing materials, and then mixed under the conditions of an open blade of 30 rpm and a Despa blade of 1200 rpm to produce an aerogel composition. Here, a planetary mixer (DN Tech, PT-005) was used for mixing.
[0122] The solids content of the prepared aerogel composition was determined to be 50 wt. % aerogel, 40 wt. % reinforcing material, and 10 wt. % polyvinyl alcohol.
[0123] 2. Battery insulation sheet manufacturing The aerogel composition prepared above was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was laminated in a sandwich type and coated by a roll rolling method. Then, the aerogel layer was formed by drying at 60°C for 24 hours to prepare a battery insulation sheet. The total thickness of the battery insulation sheet prepared was confirmed to be 1.38 mm.
[0124] Example 2 The same method as in Example 1 was used to produce the composite material, except that the first fibrous support, the second fibrous support, and the third fibrous support were added as reinforcing materials in a weight ratio of 3:4:3.
[0125] Example 3 The same method as in Example 1 was used to produce the composite material, except that the first fibrous support, the second fibrous support, and the third fibrous support were added as reinforcing materials in a weight ratio of 6:3:1.
[0126] Example 4 The same production method as in Example 1 was used, except that the first fibrous support, the second fibrous support, and the third fibrous support were added as reinforcing materials in a weight ratio of 2:6:2.
[0127] Example 5 The manufacturing method was the same as that of Example 1, except that a first fibrous support having an aspect ratio of 10, a second fibrous support having an aspect ratio of 300, and a third fibrous support having an aspect ratio of 5,000 were used as reinforcing materials in Example 1.
[0128] Example 6 The manufacturing method was the same as that of Example 1, except that a first fibrous support having an aspect ratio of 300, a second fibrous support having an aspect ratio of 100, and a third fibrous support having an aspect ratio of 1,000 were used as reinforcing materials.
[0129] Example 7 The manufacturing method was the same as that of Example 1, except that a first fibrous support having an aspect ratio of 500, a second fibrous support having an aspect ratio of 50, and a third fibrous support having an aspect ratio of 1,000 were used as reinforcing materials in Example 1.
[0130] Example 8 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) as a binder and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant were added to ultrapure water as a solvent, and then mixed under conditions of open blade 30 rpm and Despa blade 700 rpm to produce a solvent mixture. Then, aerogel having a BET value of 800 m2 / g and an average particle size (D50) of 60 μm was added to the solvent mixture, and then mixed under conditions of open blade 70 rpm and Despa blade 1500 rpm to produce an aerogel mixture. A first fibrous support having an aspect ratio of 1, a second fibrous support having an aspect ratio of 2, and a third fibrous support having an aspect ratio of 3 were added as reinforcing materials to the aerogel mixture in a weight ratio of 6:3:1, and then mixed under conditions of open blade 30 rpm and Despa blade 1200 rpm to produce an aerogel composition. Here, a planetary mixer (DN Tech, PT-005) was used for mixing.
[0131] The solid content of the prepared aerogel composition was determined to be 50 wt % aerogel, 40 wt % reinforcing material, 9.9 wt % polyvinyl alcohol, and 0.1 wt % dispersant.
[0132] 2. Battery insulation sheet manufacturing The aerogel composition prepared above was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was laminated in a sandwich type and coated by a roll rolling method. Then, the aerogel layer was formed by drying at 60°C for 24 hours to prepare a battery insulation sheet. The total thickness of the battery insulation sheet prepared was confirmed to be 1.38 mm.
[0133] Comparative Example 1 1. Aerogel Composition Preparation The solvent was ultrapure water, the binder was polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)), and the BET value was 800m 2 / g of aerogel was added and mixed to prepare an aerogel composition. Here, a planetary mixer (DN Tech, PT-005) was used for mixing.
[0134] The solids content of the prepared aerogel composition was determined to be 50 wt. % aerogel and 50 wt. % polyvinyl alcohol.
[0135] 2. Battery insulation sheet manufacturing The aerogel composition prepared above was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was laminated in a sandwich type and coated by a roll rolling method. Then, the aerogel layer was formed by drying at 60°C for 24 hours to prepare a battery insulation sheet. The total thickness of the battery insulation sheet prepared was confirmed to be 1.38 mm.
[0136] Comparative Example 2 The fabrication method was the same as that of Example 1, except that the first fibrous support having an aspect ratio of 1 was used alone as the reinforcing material.
[0137] Comparative Example 3 The fabrication method was the same as that of Example 1, except that the second fibrous support having an aspect ratio of 2 was used alone as the reinforcing material.
[0138] Comparative Example 4 The fabrication method was the same as that of Example 1, except that the third fibrous support having an aspect ratio of 3 was used alone as the reinforcing material.
[0139] (Experimental Example) Experimental example 1: SEM analysis The cross sections of the aerogel layers of the battery insulation sheets of Example 1 and Comparative Examples 1 to 4 were observed using a Hitachi S-4800 SEM, and the results are shown in Figures 3 to 7. Specifically, Figure 3 shows SEM images of Example 1, Figure 4 shows Comparative Example 1, Figure 5 shows Comparative Example 2, Figure 6 shows Comparative Example 3, and Figure 7 shows Comparative Example 4.
[0140] Specifically, in Comparative Example 1, no reinforcing material was present, and in Comparative Example 2, a first fibrous support having an aspect ratio of 1 was used alone, and it was confirmed that the fibrous support had a small average diameter. In Comparative Example 3, a second fibrous support having an aspect ratio of 2 was used alone, and it was confirmed that the fibrous support had a longer aspect ratio than in Comparative Example 2. In Comparative Example 4, a third fibrous support having an aspect ratio of 3 was used alone, and it was confirmed that the fibrous support had a longer aspect ratio than in Comparative Example 3. In contrast, in Example 1, the first fibrous support, the second fibrous support, and the third fibrous support were used in combination, and it was confirmed that the average diameters and average lengths of the fibrous supports were combined in a variety of ways.
[0141] Experimental example 2: Compression characteristic evaluation The heat insulating sheets produced in the above Examples 1 to 8 and Comparative Examples 1 to 4 were used to evaluate compression characteristics.
[0142] Specifically, using UTM equipment, we took the zero point, sandwiched each insulation sheet between 1mm thick aluminum plates, and then compressed it from 0kN to 80kN at a compression speed of 0.02mm / sec to measure the thickness change, and performed a compression test. The compression rate was calculated by the thickness reduction rate at 40kN based on the thickness of 5kN. The results are shown in Table 1 below.
[0143] Experimental example 3: Thermal insulation evaluation The heat insulating properties were evaluated using the heat insulating sheets produced in the above Examples 1 to 8 and Comparative Examples 1 to 4.
[0144] Specifically, each heat insulating sheet was placed between a pair of opposing 1 mm thick aluminum plates, then placed on a heat press, and the upper plate of the heat press was heated to 350° C., while the lower plate of the heat press was not heated and was maintained at the starting temperature of 40° C. A pressure of 20 kN was then applied to the lower plate of the heat press, and the temperature of the lower plate of the heat press after 11 minutes was measured and shown in Table 1 below.
[0145] [Table 1]
[0146] From Table 1, it was confirmed that the examples exhibited excellent compression characteristics due to improvements in porosity and orientation.
[0147] Here, from Examples 1 to 4, the evaluation results of the compression properties according to the content ratio of the first fibrous support, the second fibrous support, and the third fibrous support were confirmed, and it was confirmed that excellent physical properties were exhibited when the first fibrous support was included as a reinforcing material in an amount of 10 to 60 parts by weight, the second fibrous support was included as a reinforcing material in an amount of 30 to 60 parts by weight, and the third fibrous support was included as a reinforcing material in an amount of 10 to 60 parts by weight. Furthermore, it was confirmed that even more excellent physical properties were exhibited when the first fibrous support was included as a reinforcing material in an amount of 20 to 60 parts by weight, the second fibrous support was included as a reinforcing material in an amount of 40 to 60 parts by weight, and the third fibrous support was included as a reinforcing material in an amount of 10 to 30 parts by weight.
[0148] Moreover, from Examples 1 and 5 to 7, the evaluation results of the compression characteristics when the aspect ratios of the first fibrous support, the second fibrous support, and the third fibrous support were adjusted were confirmed, and it was confirmed that excellent compression characteristics were exhibited when the aspect ratio of the first fibrous support was 10 to 500, the aspect ratio of the second fibrous support was 50 to 300, and the aspect ratio of the third fibrous support was 1,000 to 5,000. Furthermore, it was confirmed that even better compression characteristics were exhibited when the aspect ratio of the first fibrous support was 200 to 400, the aspect ratio of the second fibrous support was 70 to 150, and the aspect ratio of the third fibrous support was 800 to 1,200.
[0149] Moreover, in Example 8, a binder and a dispersant were used in combination during the production of the aerogel composition, and it was confirmed that the compression characteristics were further improved.
[0150] On the other hand, it was confirmed that the compression characteristics were significantly decreased in Comparative Example 1, which did not contain a reinforcing material, and that the compression characteristics were decreased compared to the Examples, in Comparative Examples 2 to 4, which are cases in which a reinforcing material containing one type of fibrous support was used.
[0151] In addition, although the battery insulation sheet of the embodiment uses a fibrous support made of a material with poor insulation properties and is combined with a fibrous support with a large aspect ratio, there was no significant difference in insulation properties compared to Comparative Example 1.
[0152] Therefore, it was found that the battery insulation sheet according to the present invention has structurally enhanced mechanical properties while maintaining the insulation properties. [Explanation of symbols]
[0153] 100 Battery insulation sheet 110 First base material 120 Aerogel layer 130 Second base material 200 cells
Claims
1. A reinforcing material including two or more types of fibrous supports; Aerogel and a functional material comprising a binder, a dispersant, or a combination thereof; a solvent; The two or more fibrous supports have different aspect ratios (AR) represented by the following formula 1: AR = L / D (Equation 1) (In formula 1, L represents the average length of the fibrous support, and D represents the average diameter of the fibrous support.)
2. The aerogel composition for battery insulation sheets according to claim 1, wherein the aspect ratio difference between the two or more types of fibrous supports is 1 to 5,000.
3. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the reinforcing material comprises two or more types selected from the group consisting of a first fibrous support, a second fibrous support, and a third fibrous support.
4. 4. The aspect ratio of the first fibrous support is 1 to 500, the average diameter of the first fibrous support is 8 μm to 12 μm, and the average length of the first fibrous support is 100 μm to 3,000 μm. The aerogel composition for battery insulation sheet according to claim 3.
5. The aspect ratio of the second fibrous support is 2.5 to 2,500, the average diameter of the second fibrous support is 8 μm to 20 μm, and the average length of the second fibrous support is 50 μm to 20,000 μm. The aerogel composition for battery insulation sheet according to claim 3.
6. The third fibrous support has an aspect ratio of 300 to 5,000, an average diameter of 8 μm to 12 μm, and an average length of 3,000 μm to 50,000 μm. The aerogel composition for battery insulation sheet according to claim 3.
7. 4. The aerogel composition for battery insulation sheets according to claim 3, comprising 10 parts by weight to 60 parts by weight of the first fibrous support, 30 parts by weight to 60 parts by weight of the second fibrous support, and 10 parts by weight to 60 parts by weight of the third fibrous support, relative to 100 parts by weight of the total reinforcing material.
8. The aerogel has a BET specific surface area of 500 m 2 / g to 1,000m 2 The aerogel composition for battery insulation sheets according to claim 1, wherein the aerogel composition for battery insulation sheets has a viscosity of 1000:1 or more.
9. The aerogel composition for battery insulation sheet according to claim 1, wherein the aerogel has an average particle size (D50) of 5 μm to 200 μm.
10. 2. The aerogel composition for battery insulation sheet according to claim 1, wherein the ratio of the average particle size of the aerogel to the average length of the fibrous support is 1:1 to 1:10,000.
11. The binder comprises a water-based polymer binder, 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the aqueous polymer binder is at least one selected from the group consisting of aqueous polymers, anionic water-soluble polymers, cationic water-soluble polymers, and water-dispersible polymers.
12. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the binder is contained in an amount of 0.5% by weight to 20% by weight based on the total solid content of the aerogel composition.
13. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the dispersant is at least one selected from the group consisting of surfactants and phosphate salts.
14. The aerogel composition for battery insulation sheets according to claim 1, wherein the dispersant is contained in an amount of 0.1% by weight to 6% by weight based on the total solid content of the aerogel composition.
15. The aerogel composition for battery insulation sheets according to claim 1 , wherein the solvent is at least one selected from the group consisting of polar solvents and non-polar solvents.
16. 2. The aerogel composition for battery insulation sheet according to claim 1, wherein the reinforcing material is contained in an amount of 5 wt % to 70 wt %, the aerogel is contained in an amount of 10 wt % to 90 wt %, and the functional material is contained in an amount of 0.5 wt % to 20 wt %, based on a total solid content of the aerogel composition.
17. mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to prepare an aerogel mixture; and mixing the aerogel mixture with a reinforcing material to prepare an aerogel composition. The reinforcing material includes two or more types of fibrous supports, The method for producing an aerogel composition for battery insulation sheet, wherein the two or more types of fibrous supports have different aspect ratios (AR) represented by the following formula 1: AR = L / D (Equation 1) (In formula 1, L represents the average length of the fibrous support, and D represents the average diameter of the fibrous support.)
18. A first substrate; A second substrate; an aerogel layer formed between the first substrate and the second substrate; The aerogel layer is formed using the aerogel composition according to any one of claims 1 to 16. A battery insulation sheet.
19. Applying the aerogel composition of any one of claims 1 to 16 onto a first substrate; and laminating a second substrate on the applied aerogel composition to produce a laminate.
20. The method for manufacturing a battery insulation sheet according to claim 19, further comprising the steps of pressing and drying the laminate.
Citation Information
Patent Citations
Heat transfer suppression sheet and assembled battery
JP2022024233A
Heat insulation material
JP2022125585A
Heat transfer suppressing sheet and battery pack
JP2023098198A
Composite insulation material and manufacturing method therefor
WO2021095279A1
Thermal insulation material and method for producing thermal insulation material
WO2023058689A1